Frequency of Low Birthweight in Pregnant Women with Rheumatic Heart Disease: Low Birthweight in Pregnant Women with Rheumatic Heart Disease - Amjad, Rida; Kanwal, Shahlla; Rasheed, Tayyaba; Saleem, Humaira; Naveed, Zara; Fazal, Faiza (Pakistan Journal of Health Sciences, 2025)
Rheumatic heart disease (RHD), a complication of rheumatic fever, can cause serious valve damage and is a significant risk during pregnancy. It increases the chances of maternal and fetal complications, including low birth weight and maternal morbidity. Objectives: To determine the prevalence of low birth weight in full-term pregnancies among women diagnosed with rheumatic heart disease. Methods: A cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at Services Hospital in Lahore. A sample of 96 pregnant women aged 18–40 years with rheumatic heart disease and full-term gestation (37–41 weeks) was selected by using non-probability consecutive sampling. Relevant laboratory and radiological investigations, including ECG and echocardiography, were done. The diagnosis of RHD was established, and women were followed until delivery, and fetal birthweight was measured and assessed for LBW. The data were recorded on specially designed Performa and analyzed using SPSS version 25.0. Results: The average age of the women was 26.78 ± 6.22 years. The mean gestational age, BMI and birth weight were 38.68 ± 1.20 weeks, 24.93 ± 2.06 kg/m and 2550.13 ± 403.1 g. The fetal male gender was dominant, as 59 (61.5%). The frequency of LBW was 57 (59.4%). The analysis revealed no significant differences in the frequency of low birth weight (LBW) with age, gestational age and BMI groups (p>0.05). Conclusions: Pregnant women with rheumatic heart disease were found to have a high rate of low birth weight among their infants. However, no significant links were established between low birth weight and factors such as maternal age, gestational age, or BMI.